The Effect of Marketing Strategy, Port Facilities, and Equipment Utilization on Port Performance and Its Implications on User Satisfaction at Marunda Port - Abdul Rachman; Juneiro Marudut Halomoan Bakkara; Bhima Siswo Putro; Sajim Budi Setiawan (Dinasti Publisher, 2026)
This study investigates the integrated effects of marketing strategy, port facilities, and equipment utilization on port performance and their implications for user satisfaction at Marunda Port, Indonesia. Despite achieving a relatively high user satisfaction score (4.2/5), operational data reveal inefficiencies in asset utilization and inconsistencies in performance, indicating a gap between perceived service quality and operational effectiveness.A quantitative research design was employed using Structural Equation Modeling (SEM) with LISREL. The study utilizes both primary data collected through user surveys and secondary data derived from port operational reports (2022–2024). The results demonstrate that port facilities and equipment utilization have a strong and significant influence on port performance, while marketing strategy shows a weaker but still significant effect. Furthermore, port performance significantly affects user satisfaction, confirming its mediating role in the relationship between operational factors and customer perception. The findings reveal a critical paradox: although ship service performance (waiting time and approach time) meets operational standards, low utilization rates (BOR and YOR) indicate the presence of idle capacity, suggesting inefficiencies in land-side operations. This study contributes to the literature by providing an integrated model that simultaneously examines marketing strategy, infrastructure, and operational utilization within a port performance framework. Managerially, the study highlights the need for data-driven marketing strategies, optimization of asset utilization, and improved integration between sea-side and land-side operations to enhance competitiveness and user satisfaction.